Motivation and Satisfaction Level of Graduate Student: The Blended Learning with Peer Tutor (BL-PT) Model in New Normal Era - Nurfina Aznam; Jumadi Jumadi; Heru Nurcahyo; Yusman Wiyatmo; Riki Perdana (Universitas Negeri Makassar, 2021)
In higher Education, Graduate Students have a special characteristic of the learning process. Especially in the new normal era, Higher Education needs the best learning model that fits and comfortable for graduate students. This study aims to examine the effectiveness of Blended Learning with Peer Tutor (BL-PT) for graduate students in the new normal era, especially on the aspect of motivation and service satisfaction. It is descriptive quantitative research with the random sampling technique. In addition, this study also examined whether the level of satisfaction had an effect on student motivation in learning in the new normal period. There were 43 Graduate Students from Graduate School Program, Yogyakarta State University as participants in this study. The technique of data analyses was used comparative-descriptive and paired sample t-test using SPSS 24. The study reveals: (1) The BL-PT model has a positive impact on students motivation and service satisfaction of Higher Education; (2) there is not a significant difference in students motivation of male and female graduate students; (3) there is no significant difference of students service satisfaction level after learning with BL-PT. Learning with the BL-PT model can be an alternative for policymakers, Higher education Institution, and lecture to solve the learning model that fit and comfortable with graduate students in the New Normal Era